2019
DOI: 10.1002/mgg3.668
|View full text |Cite
|
Sign up to set email alerts
|

A genetic counseling needs assessment of Mexico

Abstract: Background While genetic counseling has expanded globally, Mexico has not adopted it as a separate profession. Given the rapid expansion of genetic and genomic services, understanding the current genetic counseling landscape in Mexico is crucial to improving healthcare outcomes. Methods Our needs assessment strategy has two components. First, we gathered quantitative data about genetics education and medical geneticists’ geographic distribution through an exhaustive com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The lack of access to medical genetic services in Latin America poses a tremendous challenge to achieving the World Health Organization (WHO) Human Genomics in Global Health Initiative goals (Bucio et al, 2019). This article describes an international model to provide genomic services to facilitate access to underserved populations and help reduce health inequalities by facilitating diagnosis and management of genetic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of access to medical genetic services in Latin America poses a tremendous challenge to achieving the World Health Organization (WHO) Human Genomics in Global Health Initiative goals (Bucio et al, 2019). This article describes an international model to provide genomic services to facilitate access to underserved populations and help reduce health inequalities by facilitating diagnosis and management of genetic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the Dominican Republic, several patients with rare diseases remain undiagnosed for several reasons including insufficient number of genetic providers, lack of disease awareness among physicians and other health care providers, and limited diagnostic and management resources. The Latin American region has limited access to genetic services and many obstacles including insufficient medical genetics education, poor patient health awareness, regional distribution of providers, and difficulties in accessing diagnostic genetic testing (Bucio, Ormond, Hernandez, Bustamante, & Lopez Pineda, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the field has grown in India and elsewhere since the course was conceived in the year 2016, there are still several challenges surrounding genetic counseling workforce development. These challenges, including relatively low awareness of the genetic counseling profession, limited opportunities for shadowing, lack of national recognition of genetic counseling as a healthcare service, and lack of establishment of practice standards, are not unique to India (Baty, 2018; Bucio, Ormond, Hernandez, Bustamante, & Lopez Pineda, 2019; Laurino et al, 2017; Ormond et al, 2018; Sun, Liang, Zhu, Shen, & He, 2019). Country‐specific studies to assess the factors that influence workforce development could be beneficial in providing a framework for growth of the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Papers published in the last 30 years (from 1991 to date) were analyzed, also relating to thematic areas different from clinical genetics, such as clinical psychology and bioethics, thus allowing an integration between the aspects of genetic diseases related to communication and bioethics and the biological and clinical ones, also considering the new techniques of genomic diagnosis [5,[12][13][14]. After a search in the literature databases by using the key words above mentioned, we found a few dozen articles related to general aspects of the communication skills of healthcare professionals and to genetic counselling, and about ten among them were of the last decade [12][13][14][15][16][17][18][19][20]. Even fewer were the studies found on prenatal counselling, as well as on communication of neonatal genetic disorders and/or single diseases, such as Down syndrome, cystic fibrosis, sickle cell anemia, thalassaemia, deafness [21][22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%